Real-world comparative study of behavioral group therapy program vs education program implemented for smoking cessation in community-dwelling elderly smokers - Pothirat,C. (Dove Medical Press Ltd., 2015)
© 2015 Pothirat et al. Background: Tobacco smoking is known to be an important contributor to a wide variety of chronic diseases, especially in older adults. Information on health policy and practice, as well as evaluation of smoking cessation programs targeting older people, is almost nonexistent. Purpose: To compare the real-world implementation of behavioral group therapy in relation to education alone for elderly smokers. Materials and methods: Elderly smokers ready to quit smoking were identified from a cohort who completed a questionnaire at a smoking exhibition. They were allocated into two groups, behavioral therapy (3 days 9 hours) and education (2 hours), depending on their preferences. Demographic data, the Fagerstrom test for nicotine dependence (FTND) score, and exhaled carbon monoxide level were recorded at baseline. Smoking status of all subjects was followed at months 3, 6, and 12. Statistical differences in continuous abstinence rate (CAR) between the two groups were analyzed using chi-square tests. Results: Two hundred and twenty-four out of 372 smoking exhibition attendants met the enrollment criteria; 120 and 104 elected to be in behavioral group therapy and education-alone therapy, respectively. Demographic characteristics and smoking history were similar between both groups, including age, age of onset of smoking, years of smoking, smoking pack-years, education level, and nicotine dependence as measured by the FTND scale. The CAR of the behavioral therapy group at the end of the study (month 12) was significantly higher than the education group (40.1% vs 33.3%, P=0.034). Similar results were also found throughout all follow-up visits at month 3 (57.3% vs 27.0%, P<0.001) and month 6 (51.7% vs 25%, P<0.001). Conclusion: Behavioral group therapy targeting elderly smokers could achieve higher short- and long-term CARs than education alone in real-world practice.